Desynchronizing Embryonic Cell Division Waves Reveals the Robustness of Xenopus laevis Development - Graham A. Anderson; Lendert Gelens; Julie C. Baker; James E. Ferrell, Jr. (Cell Reports, 2017)
The early Xenopus laevis embryo is replete with dynamic spatial waves. One such wave, the cell division wave, emerges from the collective cell division timing of first tens and later hundreds of cells throughout the embryo. Here, we show that cell division waves do not propagate between neighboring cells and do not rely on cell-to-cell coupling to maintain their division timing. Instead, intrinsic variation in division period autonomously and gradually builds these striking patterns of cell division. Disrupting this pattern of division by placing embryos in a temperature gradient resulted in highly asynchronous entry to the midblastula transition and misexpression of the mesodermal marker Xbra. Remarkably, this gene expression defect is corrected during involution, resulting in delayed yet normal Xbra expression and viable embryos. This implies the existence of a previously unknown mechanism for normalizing mesodermal gene expression during involution.